Radial Spectral Evolution of the Elsässer Variable z − in the Slow Solar Wind - Honghong Wu; Shiyong Huang; Jiansen He; Liping Yang; Zhigang Yuan (The Astrophysical Journal, 2024)
The nature of the Elsässer variable z ^− plays a significant role in the understanding of solar wind turbulence. The radial spectral evolution of z ^− observed by the Helios spacecraft suggests that z ^− has a persistent background spectrum in the low-frequency range from 0.3 to 1 au. However, the radial evolution in the near-Sun solar wind remains unknown. Here we use Parker Solar Probe measurements to analyze the averaged spectra of z ^− in the slow solar wind from 0.1 to 0.5 au and compare the results with the WIND observations at 1 au. We find that the averaged spectra of z ^− do not show the low-frequency break at the low-frequency breakpoint on the power spectra of z ^+ , magnetic field, and velocity. The energy in the frequency range of 10 ^−4 –10 ^−2 Hz demonstrates a radial decay from 0.1 to 0.5 au and keeps nearly constant to 1 au. The spectral index of z ^− gradually decreases from −1.27 at 0.1–0.2 au to −1.59 at 0.4–0.5 au and then slowly declines to −1.70 at 1 au. The radial behaviors of the ∥, ⊥ _1 , and ⊥ _2 components of z ^− in the field-aligned coordinates are similar to that of the trace of z ^− . Our findings suggest a faster radial spectral evolution of z ^− in the near-Sun solar wind and provide strong observational constraints for the solar wind turbulence model.